DEVELOPMENT OF MEASUREMENT INSTRUMENT OF AGILE ORGANIZATION MATURITY AT DEPARTMENT OF COMMUNICATION AND INFORMATION TECHNOLOGY OF WEST JAVA PROVINCE - Susatyo, Adhi
During a situation of volatility, uncertainty, complexity, and ambiguity (VUCA), the Covid-19 pandemic is one of the things that need to be considered for its impact. The lack of coordination and synergy between various lines of government in crisis management will hinder the government's response in solving these various public problems. Department of Communication and Information Technology of West Java Province (Diskominfo Jabar) needs to be an agile organization so that it can provide information that is fast, accessible, easy to understand, and respond to current conditions and changing needs. To find out the current condition, it is necessary to assess the maturity of the agile organization, the results of which was used for process improvements in the future. The assessment model developed in this study uses three dimensions, namely agile capability (sub-dimension of sensing capability and responding capability), agile enabler (human resource, structure, process, network, technology), and agile catalyst (organizational culture and operational excellence). Question indicators were developed in several stages including content analysis, semistructured interviews, and confirmatory factor analysis approaches, and resulted in 34 indicators of agile organization maturity assessment. Determination of agile level using the average score of the answers to the questionnaire with a Likert scale 4. These results will be used to determine the level of agile (nonagile, agility basics, agility transition, organizational agility). Based on the data collected by 109 respondents (29 structural officers and 80 staff), Diskominfo Jabar level is at the agility transition level. The sub-dimension that has a high value is sensing capability (3.70) while the sub-dimension that has a low value is the network (3.43) and process (3.46) so that these two sub-dimensions need to be a concern for increasing the level of agility in the future.